Use of FIB to study ZDDP tribofilms - Dawczyk,J; Ware,E; Ardakani,M; Russo,J; Spikes,H (Tribology Letters, 2018)
Focussed ion beam milling (FIB) followed by TEM has been used to study ZDDP tribofilms on rubbed steel surfaces. It has been found that the impact of high energy platinum and gallium ions during FIB causes significant morphological and structural changes to the uppermost 30–50 nm of a ZDDP tribofilm. This can be prevented by the low energy deposition of a quite thick gold layer prior to installation of the sample in the FIB facility. This problem, and its solution, have been quite widely reported in the non-tribology literature but have not previously been highlighted in the application of FIB to study tribological surfaces. It has also been found, using this gold pre-deposition method, that the bulk of the ZDDP tribofilm studied has a polycrystalline structure.